Agustín Basave Fernández del Valle, Vocación y Estilo de México. Fundamentos de la Mexicanidad, Ed. Limusa, México, 1989, 1.050 pp - García Losada, Matilde Isabel (1990)
Fil: García Losada, Matilde Isabel. Pontificia Universidad Católica Argentina; Argentina